Can urbanization improve carbon performance? - Jianmin, Zhang; Yang, Yang; Jingyuan, Huang; Xiaoxuan, Kao (Frontiers in Environmental Science, 2024)
Cities are the core carriers and key positions to achieve the dual carbon goals. Based on the panel data from 2006 to 2021, this paper analyzes the spatial autocorrelation of carbon emission performance per unit space and the impact mechanism of urbanization process on it through the spatial Durbin model. The results show that: (1) China's carbon emission performance per unit space is declining year by year. (2) There is a strong positive spatial correlation and stable path dependence on the performance of carbon emissions per unit space in each region. (3) To a certain extent, increasing the level of urbanization will reduce the carbon emission performance per unit space. (4) The urbanization process has a spatial spillover effect on the carbon emission performance per unit space of surrounding provinces, and the spatial spillover effect of industrial structure and energy consumption structure is more obvious than that of economic level, population density and urbanization rate. Based on the conclusions, this paper puts forward specific policy suggestions to reduce the carbon emission performance per unit space to help the low-carbon development of cities.